Rethinking the Roles of Universities and Polytechnics in a Regional Innovation Environment - Tomi Tura; Tuomo Uotila (European Regional Science Association (ERSA), 2005)
The article discusses the case of Finnish universities and polytechnics in re-defining their roles in regional development and especially in regional innovation environment. The so-called third task of universities, together with the regional relevance of polytechnics, has been a central topic in current regional and educational policies. The Finnish system of higher education and research is highly decentralised, including about 50 non-independent regional university units, most of them founded in order to enhance the regional effectiveness of universities. The article introduces the concept of "third task organisations” to describe these units within universities and polytechnics with regional effectiveness as their primary mission. In the article, the role of these units as both regional and scientific actors is discussed. The analysis identifies certain "non-traditional” forms of regional effectiveness of universities and polytechnics in the context of regional innovation environment. Building on this analysis, a new conceptual model of regional effectiveness is developed. As a case study, three different third task organisations within polytechnics and regional university units are analysed. It is argued that they form a challenge to the way universities, and perhaps polytechnics, too, define their role in regional innovation activities. They also problematise the common understanding of the way universities and polytechnics define their division of labour in regional development.
Keywords: 330